2007
DOI: 10.1159/000100035
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Sex Determination in Hd-rR Medaka <i>Oryzias latipes:</i> Gender Sensitivity, Thermal Threshold, Critical Period, and <i>DMRT1</i> Expression Profile

Abstract: The developmental time and thermal threshold for temperature-dependent sex determination (TSD), gender differences in temperature sensitivity, the fertility of thermally sex reversed fish, and the effect of temperature on the expression of two major sex determination/differentiation genes (DMY/DMRT1bY and DMRT1) were examined in the Hd-rR strain of medaka, Oryzias latipes. Fertilized eggs were exposed from either shortly after fertilization (8–16 cells; embryonic stages 5–6) or from middle embryogenesis (heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
75
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 41 publications
4
75
0
4
Order By: Relevance
“…Scale bar0100 μm Steroid hormone or high temperature treatments have induced complete sex reversals. These facts have indicated that an XY bipotential gonad can develop into not only a testis but also a complete ovary in medaka (Yamamoto 1958;Sato et al 2005;Hattori et al 2007). Although our XY Dmrt1 mutant finally developed into a female, in the early stage before 5 days after hatching, the germ cell number was similar to that of wild-type XY gonads, and the expression patterns of the testis-specific genes were also more similar to that of the wild-type XY gonads than the XX gonads.…”
Section: C53r/c53rmentioning
confidence: 97%
See 2 more Smart Citations
“…Scale bar0100 μm Steroid hormone or high temperature treatments have induced complete sex reversals. These facts have indicated that an XY bipotential gonad can develop into not only a testis but also a complete ovary in medaka (Yamamoto 1958;Sato et al 2005;Hattori et al 2007). Although our XY Dmrt1 mutant finally developed into a female, in the early stage before 5 days after hatching, the germ cell number was similar to that of wild-type XY gonads, and the expression patterns of the testis-specific genes were also more similar to that of the wild-type XY gonads than the XX gonads.…”
Section: C53r/c53rmentioning
confidence: 97%
“…Dmrt1 appears to be a key gene in normal testicular development because in steroid hormone treatment-induced XX sexreversed testes, Dmrt1 is expressed in the Sertoli cell lineage, similar to the expression of Dmy in XY testes (Kobayashi et al 2004). High temperatures have also induced Dmrt1 expression in XX embryos (Hattori et al 2007). However, it remains unclear whether Dmrt1 is necessary for testicular development in medaka.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that these species show a different degree of temperaturedependent sex determination (TSD; Strüssmann et al 1997b), which supposedly confers an adaptive advantage to some species in a trade-off between intraspecific competition and genetic diversity (Hattori et al 2007). Temperature-dependent sex determination could represent a differential constraint for both species, within the biogeographical range established by thermal tolerance and body size during the first winter.…”
Section: Distribution Breeding and Temperaturementioning
confidence: 99%
“…In fact, the Y chromosome-specific region is 260 kb in length (Kondo et al 2006). In addition, the genotypic sex can easily be reverted by sex hormone or high-temperature treatments (Kobayashi and Iwamatsu 2005;Sato et al 2005;Iwamatsu et al 2006;Hattori et al 2007). These results indicate that the medaka sex chromosomes are quite undifferentiated and suggest that sex determination in the medaka is at an early stage of evolution and has not reached a similar stability to that in other vertebrates like birds and mammals.…”
mentioning
confidence: 99%